2011
DOI: 10.1177/1476718x11402751
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal communication and identities options in an intergenerational art class

Abstract: This case study of multimodal pedagogies within an intergenerational (IG) art class addresses questions about the learning opportunities that were created therein and what the fixing of participants' ideas within a semiotic chain said about their facility with communicative modes and media, interests, and identity options. Key findings include: when compared to the adults' work, the children's use of media was more elaborate, experimental, and less inhibited and their designs more complex; the content of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 24 publications
0
19
2
Order By: Relevance
“…Educators within the site were knowledgeable of their students' funds of knowledge and used this information to forward emergent literacy curriculum that helped create multimodal classroom literacy events that enabled children to utilize their funds of knowledge and forward conceptualizations of themselves as competent and literate. These findings were in contrast to the half-day kindergarten study (Heydon, 2012), which emphasized print-centric literacies during teacher-directed times; more multimodal literacies when the children were at centre times; and was focused on phonological awareness and reading-levelled texts in the portions of the programme that attempted to satisfy school district-mandated assessments. The network constrained opportunities for the children's identities to inform the literacy curriculum despite the children's ability to EVERY DAY HE HAS A DREAM TO TELL 175 create alternate assemblages and enact literacy practices that more reflected their interests and knowledge.…”
Section: Literacy Curriculacontrasting
confidence: 53%
See 2 more Smart Citations
“…Educators within the site were knowledgeable of their students' funds of knowledge and used this information to forward emergent literacy curriculum that helped create multimodal classroom literacy events that enabled children to utilize their funds of knowledge and forward conceptualizations of themselves as competent and literate. These findings were in contrast to the half-day kindergarten study (Heydon, 2012), which emphasized print-centric literacies during teacher-directed times; more multimodal literacies when the children were at centre times; and was focused on phonological awareness and reading-levelled texts in the portions of the programme that attempted to satisfy school district-mandated assessments. The network constrained opportunities for the children's identities to inform the literacy curriculum despite the children's ability to EVERY DAY HE HAS A DREAM TO TELL 175 create alternate assemblages and enact literacy practices that more reflected their interests and knowledge.…”
Section: Literacy Curriculacontrasting
confidence: 53%
“…The teacher in the half-time kindergarten study (Heydon, 2012) also found the DRA time-consuming, and it took away from other parts of the classroom curriculum that were more in-line with the children's interests (e.g. outdoor play); however, with 21 children to assess and different material conditions, there were less difficulties in fulfilling the requirement.…”
Section: Assessmentmentioning
confidence: 96%
See 1 more Smart Citation
“…This was different with Tuxpaint and the collage materials where the influence of socio-cultural norms and values was less dominant. Heydon (2011) argues that children are constrained by schema regardless of the materials and resources they use in their text-making. Our data offer a perhaps more nuanced interpretation as it seems to be the case that children's creativity is influenced by different schema depending on the resource used, for instance, we saw less evidence of the girl following pre-established schemas of producing a text in the Tuxpaint and collage context where there seem to be fewer societal expectations of how a final product might look.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional resources include pens, paper, crayons and collage (Herr, 2012), each affording a multitude of options for children to express and shape their thinking and emotions (Ahn & Filipenko, 2007;Heydon, 2011). With digital resources, creativity can be expressed through sound, image, colour, movement and simulation.…”
Section: Text-makingmentioning
confidence: 99%